1998
DOI: 10.1074/jbc.273.22.13753
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Structural Analysis of the IgE Binding Sites on Ara h1, an Abundant and Highly Allergenic Peanut Protein

Abstract: Allergy to peanut is a significant IgE-mediated health problem because of the high prevalence, potential severity, and chronicity of the reaction. Ara h1, an abundant peanut protein, is recognized by serum IgE from >90% of peanut-sensitive individuals. It has been shown to belong to the vicilin family of seed storage proteins and to contain 23 linear IgE binding epitopes. In this communication, we have determined the critical amino acids within each of the IgE binding epitopes of Ara h1 that are important for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
201
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(209 citation statements)
references
References 36 publications
6
201
2
Order By: Relevance
“…5b. Interestingly, this IgE-binding epitope in the C-terminal domain of Gly m Bd 28 K occurs in a similar position to two epitopes of a peanut cupin allergen, Ara h 1 (epitope 14, D393-E402 and epitope 15, N409-K418) identified by Shin et al (1998).…”
Section: Sequence Analysis and Model Construction Of Gly M Bd 28 Kmentioning
confidence: 71%
See 1 more Smart Citation
“…5b. Interestingly, this IgE-binding epitope in the C-terminal domain of Gly m Bd 28 K occurs in a similar position to two epitopes of a peanut cupin allergen, Ara h 1 (epitope 14, D393-E402 and epitope 15, N409-K418) identified by Shin et al (1998).…”
Section: Sequence Analysis and Model Construction Of Gly M Bd 28 Kmentioning
confidence: 71%
“…This type of structure may represent a potential allergenic region in several proteins. For example, two epitopes identified in the peanut allergen, Ara h 1 (Shin et al 1998) are also located in a partially solvent exposed edge of the predicted cupin domain of the Ara h 1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Ab binding sites are thought to be dependent on the native conformation of the allergen, and epitope identification using short overlapping peptides has been criticized in that this strategy does not produce meaningful results. However, this strategy has been used to identify major epitopes of peanut allergens (37)(38)(39), and studies of milk and peanut allergens suggested (40,41) associations between IgE Ab reactivities to linear peptides and severity of disease.…”
Section: Figurementioning
confidence: 99%
“…The Ara h 1 protein is known to form a homotrimer at relatively low concentrations, and this structure has been suggested to be important to the overall allergenicity of the molecule (14). To determine the stability and types of monomer interactions that mediate the formation of a homotrimer, fluorescence anisotropy measurements were performed in the presence of increasing salt concentrations (0 -1.8 M NaCl).…”
Section: Ara H 1 Trimers Are Stable At High Concentrations Of Naclmentioning
confidence: 99%
“…However, a molecular model of the tertiary structure of the Ara h 1 protein shows that the IgE-binding sites were clustered into two main regions. In addition, Ara h 1 forms homotrimers, a physical characteristic that may be important in establishing it as an allergen (14).…”
mentioning
confidence: 99%